Begum Barve: Embodiment of subversive fantasy - Dixit, Madhuri (Studies in South Asian Film & Media, 2013)
Abstract Satish Alekar’s play Begum Barve (first performed in 1979) is a play of fantasies superimposing reality. It accommodates a universe constituted by the imagination of petty men – a female impersonator actor, a gambler and two ordinary clerks. The mixing of their imaginations creates a female fantasy-character called Nalawadebai/Sarangnayana. This is a complex exercise because the fantasy-character is inscribed on the impersonator’s male body in the wake of the physical absence of woman in the play. Nalawadebai/Sarangnayana serves as an interface for one of the clerks and the female impersonator. The character is constituted by the female impersonator’s aspiration for important female roles and the clerk’s aspiration for a normative familial life. The result is a complicated network of gendered social meanings, theatrical references and unfulfilled desires instead of any narrative. The play is unique for calling our attention to the place of mediocre female impersonators in the supposedly golden age of Marathi Sangeet Natak/musical plays. In the constitution of the fantasy-character, the play revisits contemporary cultural understanding about womanhood as exhibited and constructed by Sangeet Natak. It is important to note that the play, although much acclaimed, does not have an extensive production history. The present article proposes to examine the role of fantasies in achieving complexity of social meanings. It discusses possible reasons for the small number of performances of the play, sociology of Sangeet Natak, the subversive potential of fantasies and the theatrically constructed cultural understanding of female gender. The theoretical context of my research is informed by concepts of everyday life and embodiment.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9zYWZtLjUuMS4yNV8x